PEMBERDAYAAN TENAGA KESEJAHTERAAN SOSIAL MASYARAKAT DALAM MENINGKATKAN KETAHANAN SOSIAL MASYARAKAT - Etty Padmiati (Politeknik Kesejahteraan Sosial, 2004)
Volunteer Empowerment to Improve Social Resilient.Empowering volunteers should be seen as a recognition to their role on developing communities improving their social performance after receiving training intervention, this article attempts to present research result from Lembang, a subdistrict Bandung. This study shows that the volunteers skills improvement has a positive impact on improving social resilient, through the acceleration of social change at the community level.